A Mini Review: Visual and Auditory Perception in Dyslexia - Ali, Siti Atiyah; Fadzil, Nor Asyikin; Reza, Faruque; Mustafar, Faiz; Begum, Tahamina (IIUM Medical Journal Malaysia, 2021)
Dyslexia is a reading disorder defined as the consequences of sensory impairment which can be quite tricky in diagnosis, as many symptoms of dyslexia tend to overlap with learning disabilities such as specific language Impairment (SLI), dysgraphia, dyscalculia, and a few others. However, as research keeps on progressing, a consensus has been made suggesting that dyslexia is commonly attributed to the impairment of auditory and visual perception. This review paper intends to discuss the detailed progression of research focusing on auditory and visual perception among dyslexics.